DDRE-20. HIGH-THROUGHPUT SCREENING OF FDA-APPROVED COMPOUNDS IN GLIOMA AND GLIOBLASTOMA IDENTIFIES NOVEL THERAPEUTICS. (12th November 2021) - Wroblewski, Tadeusz; Tatman, Philip; Fringuello, Anthony; Scherer, Sam; Foreman, William; Damek, Denise; Youssef, Samy; Lillehei, Kevin; Ormond, David; Graner, Michael
Abstract: BACKGROUND: Glioma and glioblastoma comprise 28% of all primary central nervous system tumors and cause the majority of primary brain tumor deaths. Despite substantial research into the molecular pathogenesis and genetic landscape of glioma, no currently approved therapies are curative for any glioma or glioblastoma. Patients with glioblastoma have an average survival time of 12-15 months, while patients with grade III gliomas have an average survival time of 3-5 years, and patients with grade II gliomas have an average survival time of 8-15 years. The lack of a curative treatment for these tumors necessitates additional research into novel therapies. METHODS: In this study, we developed a high-throughput drug screen and culture system to identify existing FDA-approved therapies with the potential to inhibit glioma viability. RESULTS: In total, we screened 39 tumors: 21 glioblastoma, 10 oligodendroglioma, and 8 astrocytoma. Carfilzomib was the most effective compound across the cohort, decreasing the average tumor viability to 39.0% +/- 16.5%SD. Regardless of tumor grade, MGMT methylation, EGFR amplification, tumor recurrence and etiology, tumor histology, prior treatment, and patient gender, carfilzomib significantly reduced cell viability in every tumor; though was not necessarily the most effective compound in each of these groups. We found HDAC inhibition to be the most effective treatment in grade 1 astrocytomas. However, HDAC inhibition was surpassed by carfilzomib and RNA transcription inhibitors in all higher grades. Interestingly, EGFR inhibition, while significantly effective in 36 tumors, was consistently less effective than carfilzomib across the cohort, though did surpass the effectiveness of HDAC inhibition in grade III gliomas. CONCLUSIONS: FDA approved compounds can effectively inhibit glioma tumor viability. Specifically, carfilizomib holds great promise. Further in vivo studies are needed to confirm these findings.